2007
DOI: 10.1128/mcb.01080-06
|View full text |Cite
|
Sign up to set email alerts
|

The Kinase Inhibitor Sorafenib Induces Cell Death through a Process Involving Induction of Endoplasmic Reticulum Stress

Abstract: Sorafenib is a multikinase inhibitor that induces apoptosis in human leukemia and other malignant cells.Recently, we demonstrated that sorafenib diminishes Mcl-1 protein expression by inhibiting translation through a MEK1/2-ERK1/2 signaling-independent mechanism and that this phenomenon plays a key functional role in sorafenib-mediated lethality. Here, we report that inducible expression of constitutively active MEK1 fails to protect cells from sorafenib-mediated lethality, indicating that sorafenib-induced ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
225
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(248 citation statements)
references
References 72 publications
20
225
1
2
Order By: Relevance
“…The sorafenib-induced deactivation of intracellular signaling molecules was often accompanied by losses of total amounts of these proteins, and sorafenib can cause ER stress with reduced translation in leukemia cells (25). As we observed typical features of ER stress also in the sorafenib-treated HRS cell lines, it is likely that the losses of total amounts of signaling molecules are due to ER stress induced reduction in translation combined with their fast turnover rates.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…The sorafenib-induced deactivation of intracellular signaling molecules was often accompanied by losses of total amounts of these proteins, and sorafenib can cause ER stress with reduced translation in leukemia cells (25). As we observed typical features of ER stress also in the sorafenib-treated HRS cell lines, it is likely that the losses of total amounts of signaling molecules are due to ER stress induced reduction in translation combined with their fast turnover rates.…”
Section: Discussionsupporting
confidence: 48%
“…Sorafenib can cause endoplasmic reticulum (ER) stress with a general reduction of translation and caspase-3-independent cell death in human leukemia cells (25), and ER stress could thus also account for the reduction in total protein amounts of several signaling molecules and caspase-3-independent cell death in HRS cell lines. Therefore, we analyzed the effect of sorafenib on different ER stress markers in HRS cell lines by Western blotting and quantitative real-time PCR (qRT-PCR).…”
Section: Sorafenib Provokes Endoplasmic Reticulum Stress In Hrs Cell mentioning
confidence: 99%
See 1 more Smart Citation
“…Rahmani et al [39] found that constitutive activation of MEK1 failed to protect leukaemia cells from sorafenib-induced lethality. Their data suggested that endoplasmic reticulum (ER) stress represents a central component of an MEK1/2-ERK1/2-independent cell death program that is triggered by sorafenib treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment was maintained until the 7th day. In spite of the reduced cell number and block of protein synthesis 21 IgA production increased, and, as a result of ERK1/2 inhibition, expression of SPRY2 transcript was reduced (Figure 3c). This finding supports the hypothesis that a block in the MAPK/ERK leads to an increased IgA production.…”
Section: Exome Sequencing and Bioinformatics Analysismentioning
confidence: 99%